A Wreath for the Correspondence of Mikalojus Konstantinas Čiurlionis.A Few Thoughts on Radosław Okulicz-Kozaryn’s Work,the Winner of the 2025 Algis Kalėda Award - Gaidauskienė, Nida (Colloquia, 2026)
-